Advanced cervical cancer eradication by massive cytodiagnosis in the population covered by Social Security Employee - Campos Rey de Castro, Jorge (2015)
The results of the campaign cytological detection of cervical cancer conducted at the Central Hospital Employee occur. In fifteen years of work they have been discussed 97.996 women, most of them free of symptoms and signs of cervical cancer, having been diagnosed 267 cases of this neoplasm. The variation in this period occurred in the prevalence of the different stages of development of cervical cancer is discussed. In the first half, the (cancer in situ) subclinical constituted 37 percent of the cases and advanced forms (stage III and IV), together accounted for 18 percent of cases. However, in the third five-year, cases of in situ cancer they increased to constitute 52 percent, while advanced forms represent only nine percent. It is noted that the labor sector of the Social Security system, cervical cancer remains a serious social health problem, determined in part by their own biological conditions balo socio-economic status of this sector of the population, to which no add as a negative factor adjuvant lack of a systematic campaign of cytological detection of cervical cancer.